Autoinflammatory encephalopathy due to PTPN1 haploinsufficiency: a case series - Zhu, Gaofeng; Didry-Barca, Blaise; Seabra, Luis; Rice, Gillian I; Uggenti, Carolina; Touimy, Moncef; Rodero, Mathieu P; Trapero, Rolando Hernandez; Bondet, Vincent; Duffy, Darragh; Gautier, Philippe; Livingstone, Katie; et al. (The lancet, 2025)
Background - Through the agnostic screening of patients with uncharacterised disease phenotypes for an upregulation of type I interferon (IFN) signalling, we identified a cohort of individuals heterozygous for mutations in PTPN1, encoding the protein-tyrosine phosphatase 1B (PTP1B). We aimed to describe the clinical phenotype and molecular and cellular pathology of this new disease. - Methods - In this case series, we identified patients and collected clinical and neuroradiological data through collaboration with paediatric neurology and clinical genetics colleagues across Europe (Czechia, France, Germany, Italy, Slovenia, and the UK) and Israel. Variants in PTPN1 were identified by exome and directed Sanger sequencing. The expression of IFN-stimulated genes was determined by quantitative (q) PCR or NanoString technology. Experiments to assess RNA and protein expression and to investigate type 1 IFN signalling were undertaken in patient fibroblasts, hTERT-immortalised BJ-5ta fibroblasts, and RPE-1 cells using CRISPR-Cas9 editing and standard cell biology techniques. - Findings - Between Dec 20, 2013, and Jan 11, 2023, we identified 12 patients from 11 families who were heterozygous for mutations in PTPN1. We found ten novel or very rare variants in PTPN1 (frequency on gnomAD version 4.1.0 of <1·25 × 10:sup>-6). Six variants were predicted as STOP mutations, two involved canonical splice-site nucleotides, and two were missense substitutions. In three patients, the variant occurred de novo, whereas in nine affected individuals, the variant was inherited from an asymptomatic parent. The clinical phenotype was characterised by the subacute onset (age range 1-8 years) of loss of motor and language skills in the absence of seizures after initially normal development, leading to spastic dystonia and bulbar involvement. Neuroimaging variably demonstrated cerebral atrophy (sometimes unilateral initially) or high T2 white matter signal. Neopterin in CSF was elevated in all ten patients who were tested, and all probands demonstrated an upregulation of IFN-stimulated genes in whole blood. Although clinical stabilisation and neuroradiological improvement was seen in both treated and untreated patients, in six of eight treated patients, high-dose corticosteroids were judged clinically to result in an improvement in neurological status. Of the four asymptomatic parents tested, IFN signalling in blood was normal (three patients) or minimally elevated (one patient). Analysis of patient blood and fibroblasts showed that tested PTPN1 variants led to reduced levels of PTPN1 mRNA and PTP1B protein, and in-vitro assays demonstrated that loss of PTP1B function was associated with impaired negative regulation of type 1 IFN signalling. - Interpretation - PTPN1 haploinsufficiency causes a type 1 IFN-driven autoinflammatory encephalopathy. Notably, some patients demonstrated stabilisation, and even recovery, of neurological function in the absence of treatment, whereas in others, the disease appeared to be responsive to immune suppression. Prospective studies are needed to investigate the safety and efficacy of specific immune suppression approaches in this disease population. - Funding - The UK Medical Research Council, the European Research Council, and the Agence Nationale de la Recherche.
Online verfügbar 19 February 2025, Version des Artikels 19 February 2025
Gesehen am 19.09.2025